Web community builder for student organizations in UP Mindanao (WebComb) - Samonte, Precita S. (2008)
The developed system entitled ?Web Community Builder for Student Organization in UP Mindanao? presents a web site to be used by the Office of the Student Affairs ? Student Organization and Activities Section. This project identifies the duly recognized student organizations in UP Mindanao. If a recognized organization registers in the system through the main OSA-SOAS website, the system generates a default site for that organization. The configuration and database tables of each sub site are isolated from all the other sub sites. The student who requested for the generation of the site becomes the administrator of the newly created sub site generated in the sub directory of the main site. This student administrator can manage the site as he/she wants: add or manage users, change template, add content and almost all functionalities in their sub site including installation of new components, modules and templates. However, all the installed components, modules and templates are located in the same root directory and are accessible to the rest of the sub sites